2012
DOI: 10.1260/0309-524x.36.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Axial Flux Permanent Magnet Generator Design for Low Cost Manufacturing of Small Wind Turbines

Abstract: In this paper the design and manufacturing processes for coreless axial flux permanent magnet generators are described for low cost rural electrification applications, where local production of small wind turbines is considered. The process is based on already existing open source design and construction manuals, while a systematic approach to designing generators of varying nominal power and for grid connection or direct battery charging schemes is described. The manufacturing process of a 3 kW small wind tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 10 publications
(8 reference statements)
0
15
0
2
Order By: Relevance
“…Similarly, axial flux generators can be subcategorized into double stator-single rotor machines and double rotor-single stator machines, based upon the number of rotors and stators. Normally for SSWTs, an axial flux generator is preferred because it occupies lesser space in the radial direction than a radial flux generator of the same power rating (Ani, Polinder, and Ferreira;Park et al 2012;Latoufis et al 2012). A recent study by Marin et al (under review) revealed that double rotor-single stator slotless axial flux generator design provides very promising results for μSWTs.…”
Section: Generator Designmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, axial flux generators can be subcategorized into double stator-single rotor machines and double rotor-single stator machines, based upon the number of rotors and stators. Normally for SSWTs, an axial flux generator is preferred because it occupies lesser space in the radial direction than a radial flux generator of the same power rating (Ani, Polinder, and Ferreira;Park et al 2012;Latoufis et al 2012). A recent study by Marin et al (under review) revealed that double rotor-single stator slotless axial flux generator design provides very promising results for μSWTs.…”
Section: Generator Designmentioning
confidence: 99%
“…Some of the main parameters which affect the performance of an axial flux generator are number of poles, air gap between stator and rotor, shape and size of magnets, and shape of the coils. The number of pole pairs is given by the following equation (Latoufis et al 2012):…”
Section: Arc Shaped Magnetsmentioning
confidence: 99%
“…Some of the main parameters which affect the performance of an axial flux generator are number of poles, air gap between stator and rotor, shape and size of magnets, and shape of the coils. The number of pole pairs is given by following equation [58]:…”
Section: Generator Designmentioning
confidence: 99%
“…Globally 840 million people still do not have access to electricity at home (SE4All, 2017). SWTs can be produced with the skills and materials available in many developing country contexts, enabling distributed manufacture of low-cost off-grid power systems (Clausen et al, 2009;Ferrer-Martı´et al, 2010;Ghimire et al, 2010;Latoufis et al, 2012;Peterson and Clausen, 2004). The wind turbine, described by Hugh Piggott of Scoraig Wind Electric and presented in A Wind Turbine Recipe Book (Piggott, 2013), is a rugged machine designed to be manufactured using only basic tools and techniques (see Figure 1).…”
Section: Introductionmentioning
confidence: 99%